1985
DOI: 10.1210/jcem-61-2-265
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Hypothalamic Site of Action of Clomiphene Citrate in Women*

Abstract: To examine the site of action of clomiphene citrate (CC), LH and FSH pulsatile amplitude, frequency, and responsiveness to GnRH (10 micrograms, iv) were studied in 11 women during the early follicular phase of the menstrual cycle. Six women received CC (150 mg/day) on cycle days 2, 3, and 4, while 5 women received placebo tablets. Blood samples were drawn at 10-min intervals for 8 h before and after the treatment regimen on cycle days 2 and 5, respectively. All women treated with CC had multiple follicular dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(56 citation statements)
references
References 17 publications
4
52
0
Order By: Relevance
“…Subsequent efforts in the rodent to localize the anatomic sites of exogenous estra, diol's suppressive effects on LH pulse frequency have indicated that only restricted forebrain regions, e.g., the preoptic suprachiasmatic area, are involved (28). Conversely, the use of antiestrogens has provided indirect evidence that endogenous estrogen can tonically suppress LH pulse frequency in man (29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent efforts in the rodent to localize the anatomic sites of exogenous estra, diol's suppressive effects on LH pulse frequency have indicated that only restricted forebrain regions, e.g., the preoptic suprachiasmatic area, are involved (28). Conversely, the use of antiestrogens has provided indirect evidence that endogenous estrogen can tonically suppress LH pulse frequency in man (29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…It acts through binding to hypothalamic estrogen receptors, thereby blocking the negative feedback effect of circulating endogenous estrogen. 15 The use of clomiphene is found to be associated with increased incidence of multiple pregnancy. 1 Our patient had spontaneous pregnancy twice after kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
“…6 In ovulatory women, CC treatment elevates GnRH pulse frequency. 19 Women with PCOS have an anovulation with abnormally high GnRH pulse frequency. CC treatment, in anovulatory women with PCOS, increases pulse amplitude but not frequency.…”
Section: Discussionmentioning
confidence: 99%